24.1k views
5 votes
Please help asap and explain how. Tysm!!♡

Please help asap and explain how. Tysm!!♡-example-1

2 Answers

3 votes

Answer:

a = 7.9 or a = √63

Explanation:

a² + b² = c²

(The two shorter sides of a triangle are always a and b while the longer side will always be c)

So, here the longer side of this triangle is 12 and the shorter sides are 9 and a (unknown).

The equation is: a² + 9² = 12²

But to find the value of a, the formula will be 12² - 9² = a²

12² - 9² = a²

144 - 81 = a²

63 = a²

the square root of 63 = 7.9 so that means a = 7.9

User Amir Eldor
by
5.1k points
4 votes

Answer:

Explanation:

a =
√(12^2 -9^2) = √(144-81) = √(63)

We use the minus because we are searching a leg.

A leg is always shorter than the hypotenuse

User Lita
by
5.3k points